Revealing the Nature of Singlet Fission under the Veil of Internal Conversion. (16th December 2019) - Wang, Long; Bai, Shuming; Wu, Yishi; Liu, Yanping; Yao, Jiannian; Fu, Hongbing
Abstract: Singlet fission (SF) holds the potential to boost the maximum power conversion efficiency of photovoltaic devices. Internal conversion (IC) has been considered as one of the major competitive deactivation pathways to transform excitation energy into heat. Now, using time‐resolved spectroscopy and theoretical calculation, it is demonstrated that, instead of a conventional IC pathway, an unexpected intramolecular singlet fission (iSF) process is responsible for excited state deactivation in isoindigo derivatives. The 1 TT state could form at ultrafast rate and nearly quantitatively in solution. In solid films, the slipped stacked intermolecular packing of a thiophene‐functionalized derivative leads to efficient triplet pair separation, giving rise to an overall triplet yield of 181 %. This work not only enriches the pool of iSF‐capable materials, but also contributes to a better understanding of the iSF mechanism, which could be relevant for designing new SF sensitizers. Abstract : Deaktivieren durch Spaltung : Für die Deaktivierung des angeregten Zustands in Isoindigoderivaten ist eine effiziente intramolekulare Singulettfission (iSF) verantwortlich, jedoch keine schädliche interne Konversion. Die 1 (TT)‐Zustände werden nahezu quantitativ in Lösung erzeugt und können in festen dünnen Schichten weiter in zwei unabhängige freie Tripletts mit einer Ausbeute von etwa 180 % gespalten werden.